THE BUSINESS ECOSYSTEM APPROACH APPLIED TO THE INDUSTRIAL HERITAGE MANAGEMENT - Perfetto, Maria Concetta; Presenza, Angelo (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2016)
The purpose of our work is to deepen the knowledge about the Business Ecosystem approach and apply it to the management of Industrial Heritage (IH). Our approach comprises new organizational forms that do not easily fit with the traditional business models. The IH capitalization consists in the ability to tie the meaning and destiny of IH to contemporary processes of local development, in which the policies of reuse are contextualized in wider processes of socio-economic and territorial transformation. The processes of IH reuse and capitalization involve the activation of initiatives able to reinvent through creativeness and innovativeness those repositories of knowledge looking for new and sustainable purposes of utilization. This revitalization process involves economic, social and cultural transformations that require sophisticated management strategies. After a review of the literature, a case study is presented and analyzed to reflect on the stakeholders that compose the Industrial Heritage Business Ecosystem (IHBE) and their interrelated interactions. The analysis of the case reveals that an efficient project of IHBE relies on a system capable to link the creative idea, the organization and the business ecosystem in order to reach the market satisfaction; the IHBE success is related to the ability to co-evolve and valorize the actors involved in the project, generating a series of trust relationships primarily focused on the coproduction. Conclusions, theoretical and practical implications conclude the paper.